Development of Vocabulary Assessment Instrument Based on Information on Writing Materials for Explanatory Texts of 11th Grade Students Senior High School - Siti Hazizah Siregar (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to analyze the development of information-based vocabulary assessment instruments on writing explanatory text material for grade XI high school students. This research will be conducted in 11th grade of Senior High School Panai Tengah. This research was conducted in the 2019/2020 academic year for 3 months from August 2019 to October 2019. The 6-month research activity began from field observations to determine the needs analysis to the thesis examination. The results of the trial of the information-based vocabulary assessment instrument on the explanatory text material were captured through the teacher's response questionnaire about the practicality of the developed assessment instruments. The practicality gained was captured through a questionnaire distributed to two teachers who studied Indonesian. The teacher's response questionnaire to find out the practicality of the assessment instruments developed included three sub-components of the assessment, namely aspects of attractiveness, aspects of ease, and aspects of readability. The attractiveness aspect gets a percentage value of 96% in the "excellent" category. Linguistic aspects get a percentage value of 100% with the category "excellent." And the last aspect is the aspect of convenience which gets a percentage value of 85% with the category "excellent."